marital satisfaction according to spouse’s smoking status - Hasani Fard, Amir Hosein; Hamdieh, Mostafa; Abed, Farhang; Alikhani, Shiva; Farahi, Foojan; Chinifroush-asl, Mir Mehdi (Archives of Men's Health, 2020)
Introduction: One of the key aspects of mental health is one’s overall health and lifestyle. Longitudinal studies have shown that dissatisfaction with life causes long-term health damage and increases mortality, suicide tendency, unintentional injuries, disability at work, and diseases such as those of cardiovascular nature. Amongst all forms of satisfaction, that of marital is of utmost importance. On a separate note, inhalation of cigarette smoke exposes passive smokers to many chemical and toxic carcinogens, and it can negatively affect the non-smokers present. Furthermore, in psychiatric counseling sessions, many women report that they hate smoking. If we can show that inhaling cigarette smoke in men can have an impact on marital satisfaction, it can increase the consistency of family foundations and have positive effects on the health and spirit of family members by informing families. Methods: In this study, 200 housewives, who had smoking husbands that smoked at home, were subjected to pre-determined conditions, alongside 200 housewives who had non-smoking husbands and were therefore not exposed to smoking by their husbands at home. They were divided into two groups and were assessed by Marital Conflict Questionnaire (MCQ). For a closer look at the level of marital satisfaction, the questionnaire results were divided into three subgroups which were marked as low, moderate, and good. Results: After calculating the total score of the questionnaire and statistical analysis, the results showed a higher rate of marital satisfaction in women who had non-smoking husbands compared to those who had smoking husbands and this difference was considered significant at P-value <0.001. Conclusion: Inhaling cigarette smoke in men in the family environment may seem to make a good impression on the smokers, but as the results of our study suggest, it also has adverse effects on marital satisfaction.